2016
DOI: 10.1038/srep29480
|View full text |Cite
|
Sign up to set email alerts
|

The integrative role of orexin/hypocretin neurons in nociceptive perception and analgesic regulation

Abstract: The level of wakefulness is one of the major factors affecting nociception and pain. Stress-induced analgesia supports an animal’s survival via prompt defensive responses against predators or competitors. Previous studies have shown the pharmacological effects of orexin peptides on analgesia. However, orexin neurons contain not only orexin but also other co-transmitters such as dynorphin, neurotensin and glutamate. Thus, the physiological importance of orexin neuronal activity in nociception is unknown. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 73 publications
1
81
0
1
Order By: Relevance
“…Our data provide strong evidence for a key role of orexin neuron activity in millisecond-scale sensorimotor transformations (Figures 5 and 6) as well as self-initiated movement and diverse mobile behaviours ( Figure 1). Previous work has demonstrated that orexin neurons have sensory responses (González et al, 2016a;Hassani et al, 2016;Inutsuka et al, 2016;Mileykovskiy et al, 2005), and here we have demonstrated that these responses have a function in coupling sensation to action. To our knowledge, this is the first hypothalamic neuronal population shown to mediate a rapid sensorimotor transformation, similar to those seen in the neocortex (Ferezou et al, 2007;Svoboda and Li, 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our data provide strong evidence for a key role of orexin neuron activity in millisecond-scale sensorimotor transformations (Figures 5 and 6) as well as self-initiated movement and diverse mobile behaviours ( Figure 1). Previous work has demonstrated that orexin neurons have sensory responses (González et al, 2016a;Hassani et al, 2016;Inutsuka et al, 2016;Mileykovskiy et al, 2005), and here we have demonstrated that these responses have a function in coupling sensation to action. To our knowledge, this is the first hypothalamic neuronal population shown to mediate a rapid sensorimotor transformation, similar to those seen in the neocortex (Ferezou et al, 2007;Svoboda and Li, 2018).…”
Section: Discussionsupporting
confidence: 74%
“…Orexin neurons are critical regulators of arousal and whole body metabolism (Adamantidis et al, 2007;Yamanaka et al, 2003), that are commonly thought to act on a slow timescale. However, unit recordings (Hassani et al, 2016;Lee et al, 2005;Mileykovskiy et al, 2005;Takahashi et al, 2008) and averaged population recordings with fiber photometry (González et al, 2016a;Inutsuka et al, 2016) have shown that orexin neurons respond to sensory stimuli, and that they can change their spike output on the millisecond timescale. Because the activity of orexin cell ensembles has not been recorded before at single-cell spatial resolution, it is unclear what proportion of orexin neurons are responsive and how this activity is coordinated between them.…”
Section: Introductionmentioning
confidence: 99%
“…Clear evidence for a specific role of orexins in nociceptive processing was initially demonstrated by prepro‐orexin knockout mice, demonstrating no alteration in basal nociceptive thresholds between wild type and transgenic mice; however, following peripheral inflammation orexin knockout mice demonstrated significantly greater hyperalgesia. This finding was recently supported using novel pharmacogenetic approaches and temporally controlled ablation whereby orexinergic activation was directly associated with pain perception and orexinergic neurons actively participated in analgesic responses …”
Section: The Utility Of Targeted Orexinergic Modulation For Headachementioning
confidence: 99%
“…This finding was recently supported using novel pharmacogenetic approaches and temporally controlled ablation whereby orexinergic activation was directly associated with pain perception and orexinergic neurons actively participated in analgesic responses. 85 The first evidence for a potential role of orexinergic modulation in migraine was stimulated by the identification of a differential response of TCC neurons to dural-evoked nociceptive responses following microinjection of orexin A and B into the posterior hypothalamus. 51 In agreement with previous studies, orexin A was anti-nociceptive whereas orexin B was pro-nociceptive, suggesting a complex organization based on the individual neuropeptides.…”
Section: The Utility Of Targeted Orexinergic Modulation For Headachementioning
confidence: 99%
“…Orexin functions as a neuropeptide that binds to G-protein coupled receptors (GPCRs), termed orexin 1 (OX1R) and orexin 2 (OX2R) receptors, and participates in multiple physiological responses including feeding behaviour, sleep/wakefulness, and perception of pain1456. To regulate such intricate physiological responses, orexin neurons receive and integrate diverse synaptic inputs from many brain regions, including serotonergic neurons in the midbrain raphe nuclei7.…”
mentioning
confidence: 99%